Comparison of the Effect of Four Different Abutment Screw Torques on Screw Loosening in Single Implant-Supported Prosthesis after the Application of Mechanical Loading - Behnaz Ebadian; Amirhossein Fathi; Saba Khodadad (Hindawi Limited, 2021)
Background. The complications of implant-supported prostheses can be classified into mechanical and biological ones, one part of which is associated with screw loosening. This study was aimed to compare the effect of four different abutment screw torque techniques on screw loosening in single implant-supported prostheses following the application of mechanical loading. Materials and Methods. In this experimental study, a total of 40 implants in acrylic blocks (6 × 10 × 20 mm) were mounted perpendicular to the surface. They were then randomly divided into four groups: (1) torquing once with 30 Ncm, (2) torquing three times with 30 Ncm and 5-minute intervals, (3) torquing once with 30 Ncm, opening the screw, and retorquing with 30 Ncm, and (4) torquing once with 35 Ncm. The torque values were confirmed by using a digital torque meter. Then, the samples underwent a force (2 cps, 0.453-11.793 kg) for three hours before the measurement of detorque values. The screw loosening force (torque) was then measured and recorded. The obtained data were analyzed by SPSS (version 22) software using one-way ANOVA and Tukey post hoc test at a 5% error level. Results. The maximum mean detorque values of the abutment screws in single implant-supported prostheses were reported for groups 4 (27.8 ± 1.3), 1 (26.8 ± 1.3), and 3 (25.1 ± 1.3), and the minimum mean detorque value was found in group 2 (24.9 ± 1.2). Moreover, no significant difference was observed between groups 2 and 3 (p>0.05), but a significant difference was found between groups 1 and 3 and other groups (p<0.05). Conclusion. The increase in the torque value increased the torque loss. However, the detorque value in group 4 showed the least difference with the value recommended by the manufacturer (30 Ncm).